Digital Literacy and Self-Control as Predictors of Ethical Online Behavior among Generation Z - Noer Laili, Lilik; Yudha Sasana, Mada; Al Haariz, Muhammad; Alfi Syahrin, Muhammad (JURNAL PENELITIAN DAN EVALUASI PENDIDIKAN, 2026)
The rapid advancement of digital technology has transformed patterns of communication and social interaction, particularly among Generation Z as digital natives. Although digital media offers extensive educational and social benefits, it also presents ethical challenges such as misinformation, cyberbullying, hate speech, and impulsive online behaviour. This study aims to examine the effects of digital literacy and self-control on ethical online behaviour among Generation Z and to analyse their combined predictive power. This research employed a quantitative cross-sectional survey design involving 130 students of MTs Bilingual Muslimat NU Pucang Sidoarjo, Indonesia, selected from a population of 191 students using proportionate random sampling. Data were collected through a structured questionnaire using a five-point Likert scale, and the instruments were confirmed to be valid and reliable. Multiple linear regression analysis was used to test the proposed hypotheses. The results indicate that digital literacy has a positive and significant effect on ethical online behaviour (B = 0.477; p < 0.001), suggesting that higher levels of digital competence and ethical awareness contribute to more responsible online conduct. Self-control also shows a positive and significant influence (B = 0.324; p < 0.001), highlighting the role of emotional regulation and impulse control in shaping ethical behaviour in digital environments. Simultaneously, digital literacy and self-control explain 48.1% of the variance in ethical online behaviour (R² = 0.481; p < 0.001), indicating that ethical online behaviour emerges from the integration of cognitive competence and self-regulatory capacity. These findings emphasise the importance of integrating digital literacy education with self-control and character development programs to foster ethical online behaviour among Generation Z.